American Indian biographies - Markowitz, Harvey; Barrett, Carole A. (Magill's choice., 2005)
Contains biographical sketches, ranging in length from 300 to 3,000 words, on figures in North American Indian history, extending from the arrival of European colonists on North American shores to the early twenty-first century.